Outcomes Following Liver Transplantation for Patients with Alcohol- Versus Nonalcohol-Induced Liver Disease - Dory Abosh; Barry Rosser; Kelly Kaita; Rose Bazylewski; Gerald Minuk (Canadian Journal of Gastroenterology)
OBJECTIVE: To document and compare the outcomes of adult patients who received liver transplants for alcohol- and nonalcohol-induced liver diseases who attended a liver transplantation follow-up clinic in an urban, nontransplantation centre at a time when no formal alcohol abuse program for transplant candidates and/or recipients was offered.